HUBUNGAN MINAT BELAJAR DENGAN HASIL BELAJAR KOGNITIF BIOLOGI SISWA KELAS XI DI SMAN 7 LUWU - Qhadriah Dahrun, Nur; Daud, Firdaus; Rahmat Saleh, Andi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to determine the relationship between learning interest and cognitive biology learning outcomes among Grade XI students at SMAN 7 Luwu. A mixed-methods approach with an explanatory sequential design was employed, involving 61 students selected via a saturated sampling technique. Data on learning interest were collected through questionnaires, while data on cognitive learning outcomes were obtained from grade records and supplemented by interviews with teachers and students. Data analysis was conducted using the Pearson Product Moment correlation. The results showed an average learning interest score of 49.56 (categorized as very high) and an average cognitive learning outcome score of 86.37 (categorized as high). The correlation test yielded an r-value of 0.287 with p = 0.025 (p < 0.05), indicating a positive and significant relationship between learning interest and cognitive biology learning outcomes, albeit with a low degree of correlation.